PENANGANAN TUNGGAKAN DANA BERGULIR (NON PERFORMING LOAN) PASKA PELAKSANAAN PNPM MANDIRI PEDESAAN - Nuraini, Siti (Universitas Airlangga, 2016)
The purpose of this research to looking for handling problems after theimplementation of PNPM Mandiri Rural especially for arrears (non performingloan ) revolving funds that has become asset the community. For the first time,monitoring and evaluation originally carried out by the external but after theprogram is will be by the community.This research used methodology qualitative totechnique observation, interviews and focuss group discussion (FGD).This resultindicates that the development of asset revolving funds activity management units(UPK) is 56 %.Arrears revolving funds accidents was at the beginning of theprogram because the weak of institutional and monitoring to thebeneficiaries.Handling arrears (non performing loan ) should be conducted in afamily spirit have not yet decided to the police.This advice especially to the localgovernment is to supervision and strengthening institutional owned by the activitymanagement units (UPK) becauserevolving funds managed quite large and gavebenefits received by the public is also quite a lot.